Associations of steroid-specific antibodies and polymorphisms of cytokine genes with tumor proliferation in breast cancer patients - E. G. Polenok; L. A. Gordeeva; M. V. Kostyanko; A. V. Antonov; P. V. Bayramov; N. E. Verzhbitskaya; V. N. Zakharov; G. I. Kolpinskiy; A. N. Glushkov (Медицинская иммунология, 2025)
Earlier it was shown that actively proliferating tumors with Ki-67 positive cells > 20% are more frequently detected in breast cancer patients (BC) with high serum levels of autoantibodies against estradiol and progesterone (IgA1-E2 and IgA1-Pg), and less common in BC with high levels of corresponding antiidiotypic autoantibodies (IgG2-E2 and IgG2-Pg). The genetic factors for development of these auto-antibodies are still unknown. The purpose of this study was to search for associations between polymorphic loci of the IL1A (rs1800587), IL1B (rs16944), IL6 (rs1554606, rs1800795, rs1800796), IL10 (rs1800896) and TNFA (rs1800629) genes and serum levels of IgA1-E2, IgA1-Pg, IgG2-E2, IgG2-Pg as compared with tumor levels of Ki-67positive cells in BC patients. Antibodies and antiantibodies specific to steroid hormones were assessed by means of ELISA technique, being studied in 661 BC stage I patients, and in 741 patients with stage II-IV disease. Single nucleotide polymorphisms of cytokine genes were determined by PCR technique in DNA isolated from lymphocytes. Ki-67-expressing cells were detected using immunohistochemical technique in tumor samples of 484 stage I BC patients, and in 551 patients with disease of II-IV stage. Higher levels of Ki-67 positive tumor cells were found in patients with stages II-IV breast cancer carrying GG genotype of IL6 gene (rs1800796) more frequently than in patients with the CG genotype (63.3% vs. 48.6%, p = 0.02). Three immunological phenotypes have been found according to individual combinations of studied idiotypic and antiidiotypic antibodies differently associated with tumor proliferation in BC patients (stage II-IV). Highly proliferating tumors (Ki-67 positive cells > 20%) were found in 61.5% BC patients with “neutral” immunological phenotype; in 47.3% BCP with “inhibition” phenotype (p = 0.02 vs. “neutral”), and in 71.2% (p = 0.047 vs. “neutral”, p < 0.001 vs. “inhibition”). The frequency of BC patients with any not changed from I to II-IV stages of the disorder. The “stimulating” phenotype was found more often in carriers of the GG IL6 genotype (rs1800796) than in persons with CG genotype (26.8% vs. 19.1%, p = 0.028). In conclusion, immunomodulation of tumor proliferation by idiotypic and antiidiotypic antibodies specific to steroid hormones was associated with functional polymorphism rs1800796 of the IL6 gene.